Understanding teachers’ career choices: Narratives from international in-service teachers of English as a Foreign Language (EFL) - Olan, Elsie L.; Belló, Paula (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This international study investigated factors that shape individuals’ decisions to become English teachers as a Foreign Language (EFL). Using a qualitative narrative study design, data was collected from 25 in-service teachers in two different groups from Middle Eastern, Asian, African and Latin American countries. Twelve of the participants were recipients of the US Department of State via Bureau of Educational and Cultural Affairs (ECA) scholarship and participants in the Teaching Excellence and Achievement (TEA) program organized by IREX. The other thirteen participants were non-funded in service EFL teachers. Results indicated that EFL in-service teachers use narratives and counter narratives to refer to their career decision process. In-service teachers reflect and base their career decision-making process within three comprehensive areas, i.e. personal realization, support system and access to education. This international longitudinal study was designed to explore the areas that influence EFL teachers’ motivations and perceptions when choosing the teaching profession.